The challenges of obtaining consent in emergency care research - Fatovich, Daniel; Finn, Judith; Webb, Steve; MacDonald, Stephen (2020)
It is not possible to consent a patient for emergency research in advance of their acute illness, as the clinical events are not predictable. We discuss the problems of undertaking research in an emergency care setting, where patients lack the capacity to provide consent but require time critical interventions. There is no settled definition of what constitutes ‘research’ as distinct from ‘treatment’. In fact their relationship is a continuum that demands similar level of oversight for both. We provide examples where the usual requirement for written informed consent means the trial underestimated benefits, because the treatment would normally be given without delay. Consent rituals that delay the start of trial treatments may in fact be unethical and offend against the Declaration of Helsinki. Clinical research delivers improved patient outcomes irrespective of the randomised group. This is currently under threat by a lack of consistency across jurisdictions in the interpretation of the relevant legislation.